Analisis Mazhab Hanafi Tentang Jual Beli Tanah Tanpa Tanamannya: Analysis of the Hanafi Mazhab Concerning Buying Land Without Plants - Rosmita; Santi Sarni; Aisyah Nurul Afifah (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2026)
This study aims to analyze the Islamic legal perspective on the practice of buying and selling land without plants growing on it, as well as the views of the Hanafi school of thought on this matter. The questions are: First, what is the Islamic legal perspective on the practice of buying and selling land without plants growing on it? Second, how is the Hanafi school of thought analyzing the Hanafi school of thought on buying and selling land without plants growing on it? This study used a qualitative approach with textual study (Library Research) and normative and phenomenological analysis. The results show that, from the Hanafi school of thought, the sale of land without plants growing on it can be explained as follows: First, in the practice of buying and selling land that includes plants, according to Islam, the plants are sold along with the land. This is based on the understanding that plants are part of the land, so that ownership of the land and plants is transferred to the buyer. This is also in line with the customary practice ('urf) of society, which considers plants to be an inseparable part of the land, unless the contract stipulates otherwise. Second, according to the Hanafi school of thought, plants growing on land do not automatically become part of the land sale unless expressly stated in the contract. This view emphasizes the importance of clarity regarding the object of the contract in a sale and purchase transaction. Therefore, although the majority of scholars believe that the land sold includes the building and the plants on it, it is advisable to state the ownership of the plants in official documents, such as a land certificate or a deed of sale, to avoid future disputes and maintain prudence (iḥtiyāt).